ESKATOLOGI DALAM PANDANGAN IBN RUSYD - Muslihin, Muslihin (LPPM IAIN Parepare, 2017)
One thing that is certain in this world is accountability. The afterlife is a continuation of the end of life in the world. In this afterlife, man will be responsible for his actions while living in the world. This article aims to describe Ibn Rushd's eschatological construction. Ibn Rushd is a Muslim philosopher who tries to prove that between wisdom (philosophy) and sharia is not an interesting contradiction to be studied in more depth. In other words, he was the philosopher who intensely attempted this integration, the integration of reason and revelation. Ibn Rushd solved his eschatological problems by the way of philosophical thought and divination.